Pyramids of Power: A Statistical Snapshot of Women in Post-Secondary Education in Canada and Some Ideas for Making Change - Robbins, Wendy; Simpson, Vicky (Atlantis)

(untitled) (Mount Saint Vincent University, 2009)
Women students have made impressive progress in Canadian post-secondary institutions, but change in the professoriate has not kept pace. Systemic biases in university policies and working conditions, problematic notions of excellence, and prejudicial "gender schemas" remain as barriers.